Whose reading matters? Rereading Exodus 1 in the context of African (South African) women. Issue 2 (2nd May 2020) - Masenya (Ngwan'a Mphahlele), Madipoane
Abstract: The narrative of the interaction of African (South African) women and the Bible is first situated within the framework of the folktale of the Lion and the Rabbit. The theme of the multiplication of (male) babies as featured in Exodus 1 is then re‐read through the hermeneutical lenses of African (South African) women's experiences. If Exodus 1 is read in family‐oriented cultures like that of ancient Israel and Africa, what insights may be gleaned? Which reading(s) may emerge? Will the resultant readings matter especially to African (South) African women? The preceding questions, will be engaged with in this essay.